Analisis Curah Hujan Ekstrim untuk Penentuan Ketersediaan Air Tanah di Kecamatan Amahai, Kabupaten Maluku Tengah - Frans Thomas Latuny; Rhony Einstein Ririhena; Elia Leonard Madubun (Fakultas Pertanian, Universitas Pattimura, 2022)
The influence of global phenomena on Extreme rainfall in the Moluccas is El Nino and La Nina. This phenomenon is closely related to the reduction of rainfall and excess rainwater which has a systematic impact on the availability of groundwater and also on the production of food crops. This study aims to obtain data on the impact of El Nino and La Nina phenomena by calculating the availability of groundwater in Amahai district. The study used data on climatic elements from the Amahai Meteorological Station, then the data was processed using statistical calculations to obtain normal rainfall and the average distribution of precipitation in the growing season and planting time.